2016
DOI: 10.1016/j.gie.2016.03.1469
|View full text |Cite
|
Sign up to set email alerts
|

Per-oral endoscopic myotomy, 1000 cases later: pearls, pitfalls, and practical considerations

Abstract: The dissemination of this information serves as a foundation for new POEM operators and as a catalyst for more-experienced operators to further refine and advance their POEM skills and stimulate international discourse and collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 13 publications
1
58
0
2
Order By: Relevance
“…The risk factors for major adverse events were short experience with the technique (<1 year), air insufflation, and mucosal edema. The results of this study are consistent with those reported in the literature [3,4,31]; also, this study confirmed that the use of CO 2 dramatically decreases the risk of complications.…”
Section: Overall Major Adverse Eventssupporting
confidence: 92%
See 1 more Smart Citation
“…The risk factors for major adverse events were short experience with the technique (<1 year), air insufflation, and mucosal edema. The results of this study are consistent with those reported in the literature [3,4,31]; also, this study confirmed that the use of CO 2 dramatically decreases the risk of complications.…”
Section: Overall Major Adverse Eventssupporting
confidence: 92%
“…For the mucosal closure it is important to follow several advices that have been described by Bechara et al in their recent experience of 1,000 patients [31]. It is crucial to emphasize the importance of symmetrical clip deployment.…”
Section: During the Proceduresmentioning
confidence: 99%
“…An endoscopic submucosal injection of dyed saline is followed by a mucosal incision, and subsequent creation of a submucosal tunnel to expose the circular muscle fibers at a length 2-3 cm beyond the LES. Selective circular muscle myotomy is then carried out under direct visualization, and the mucosa is closed with clips [47]. Advancements in technology as well as refinements in technique have led to safer procedures, as well as decreased operative time.…”
Section: Treatmentmentioning
confidence: 99%
“…POEM has even been performed successfully on refractory cases of achalasia following previous balloon dilation or laparoscopic Heller myotomy [52][53][54][55]. These cases should only be treated by highly experienced operators [47]. The advantage of POEM over surgical myotomy is that the length of the myotomy from the esophageal to gastric side can be adjusted freely to suit the individual case.…”
Section: Treatmentmentioning
confidence: 99%
“…Indeed, the pioneering Japanese center for refining the technique recently summarized technical pearls and pitfalls on performing POEM gleaned from their first 1000 procedures. 2 Uncontrolled outcomes data have been very promising comparing POEM with the standard surgical treatment for achalasia, laparoscopic Heller myotomy (LHM). 3 However, concerns remain regarding post-POEM reflux, the durability of the procedure, and the learning curve for endoscopists adopting the technique.…”
mentioning
confidence: 99%